Impacting the Sensory Experience of Products Experimental Studies on Perceived Quality - Cowen-Elstner, Christine (Forschungs-/Entwicklungs-/Innovations-Management, 2018)
Based on two experimental studies Christine Cowen-Elstner explores the possibilities of influencing the sensory product perception and thereby also the perceived product quality. The results of her studies not only show that this influence is happening but also that the expectation and experience of an individual play a crucial role in this context. Based on these findings she then develops recommendations for product design and communication. Contents Quality perception and possible influences Sensory marketing and the five senses Possibilities for unconscious consumer influence Empirical investigation of the environmental influence Experimental research of the importance of product packaging Target Groups Researchers, lectures and students of marketing, product development, communication, and business management Practitioners and consultants in the field of marketing, product management and marketing communication The Author Dr. Christine Cowen-Elstner received her doctorate at the Institute of Innovation Marketing at the Hamburg University of Technology under Prof. Dr. Christian Lüthje. She presently works as a marketing specialist. .